Tanpa Standar, Tanpa Akuntan: Potret Buram Tata Kelola Keuangan Yayasan Nirlaba di Kabupaten Tanah Datar - Sri Adella Fitri; Salwa Assyfa Yusri; Suci Rahmadani; Viola Agnesya; Zainia Jannah; Indri Nazwah Ari Syahputri (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the implementation of Interpretation of Financial Accounting Standards (ISAK) 335 in the financial management of non-profit foundations in Tanah Datar Regency, particularly in Rambatan and Sungai Tarab Districts. The study employed a qualitative case study approach using semi-structured interviews with financial managers from four foundations: Yayasan SLB Az-Zahra, Yayasan Darul Ulum/Darul Hafazah, Yayasan Daarut Tahfidz Al-Sulaiman, and Yayasan Jabal Rahmah. Data were analyzed using thematic analysis to identify the level of ISAK 335 implementation and the factors affecting its adoption. The findings reveal that none of the foundations have implemented ISAK 335 in preparing their financial statements. The main obstacles include the limited availability of personnel with accounting expertise, simple bookkeeping practices focused only on cash inflows and outflows, inadequate understanding of accounting standards for non-profit entities, and dependence on a single source of operational funding. Consequently, the financial statements do not comply with applicable accounting standards, resulting in low levels of transparency, accountability, and financial information quality. This study recommends enhancing the capacity of financial managers through training, gradually adopting ISAK 335, utilizing digital bookkeeping systems, and diversifying funding sources to strengthen accountable financial governance and ensure organizational sustainability.